Health services for cancer survivors practice, policy and research - Feuerstein, Michael; Ganz, Patricia (Springer, 2011)
Health Services for Cancer Survivors Practice, Policy, and Research Michael Feuerstein and Patricia A. Ganz, editors Between early detection and current medical advances, more cancer patients are living longer post-treatment. But all too often, survivors? lives are complicated by medical, psychosocial, and economic challenges that their providers downplay as the ?new normal.? Health Services for Cancer Survivors replaces this scenario with an integrative, evidence-based framework for improving the health of survivors over the long term, across clinical settings and specific diagnoses. Emphasizing an interdisciplinary team approach, contributors review the current state of survivor care and model a proactive future. Human factors, particularly in the areas of symptoms and symptom reporting, health costs, and individualized care, are highlighted as keys to survivors? health, well-being, and functioning. The book offers diverse perspectives, informative data, and real-world case studies as it: Defines quality health care in the context of cancer survivor experience. Introduces the Cancer Survivorship Care Plan, a first-steps strategy for integrating survivor care. Pinpoints specific areas for improvement, including symptom management, health behaviors, rehabilitation, psychological well-being, and disparities in health care access and delivery.  Outlines practical strategies for optimizing primary, oncological, palliative community-based, and end-of-life care. Provides detailed information on epidemiology, health economics, and other areas critical to clinical decision-making. Analyzes the new health care reform measures as an opportunity to reform survivor care. Health Services for Cancer Survivors is essential, stimulating reading for a wide range of practitioners, including primary care physicians, health psychologists, social workers, nurses, physical and occupational therapists, and public health professionals.